A Study on Derivatives Market in India:Current Scenario and Future Trends - Kapadia, Riddhi (2006)
The derivative market has become multi-trillion dollar markets over the years. Derivatives are financial commitments indexed or linked in some capacity to changes in the value of underlying assets. The bulk of the derivatives trading internationally are linked to currencies and interest rates, other derivatives are linked to equity or equity indices. A very small volume of derivatives, compared to the total, is indexed to traditional commodities. Small by comparison to other derivatives markets, these commodities-indexed derivatives markets are large compared to the underlying physical commodity markets.